The Auxiliary State Organ Authorities in Indonesia: The Constitutional Implications of Law No. 19 of 2019 Concerning KPK - Zaini, Ahmad; Ridho, Moh. Zainor (Potret Pemikiran, 2023)
This article examines an auxiliary state organ that has mixed functions in carrying out its duties, namely semi-legislative and regulatory, semi-administrative, and even semi-judicative. The KPK has a relationship with the legislature in terms of selecting its membership apparatus. This research analyzes the KPK authority in Indonesia after Law No. 19 of 2019 concerning the KPK and the constitutional implications of Law No. 19 of 2019 concerning the Corruption Eradication Committee. The Law No. 19 of 2019 concerning the Corruption Eradication Committee was used as the main source to answer the research questions. The results of this research explain that KPK is an auxiliary state organ whose position is under the independent executive family, free from any interference in carrying out its functions and authority. This is an implication of Constitutional Court Decision Number 36/PUU-XV/2017, which was then used as the basis for the creation of Law No. 19 of 2019 concerning the second amendment to Law No. 30 of 2002 concerning KPK, and the implication of changing the position of the KPK is that the functions and authorities of the KPK also change, thus eroding the functions and authorities of the KPK that existed before, coupled with the existence of a Supervisory Board, which is considered to further weaken its functions and authorities.